Independence of the General Election Commission and Election Supervisory Board for Democratic Elections - Ridwan Syaidi (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
The Constitution explicitly states that to achieve the national ideals and objectives, General Elections need to be held to elect members of the People's Representative Council, members of the Regional Representative Council, the President and Vice President, and to elect members of the Regional People's Representative Council, as a means of realizing the sovereignty of the people and producing representatives of the people and a democratic state government based on Pancasila and the 1945 Constitution of the Republic of Indonesia. The organizers of elections, as regulated in Law Number 7 of 2017 concerning General Elections, are stated to be the Election Commission, the Election Supervisory Body, and the Council of Election Organizer Honor as a unified function of Election Organization. Doubts about the independence of the general election commission continue to be questioned by parties who dislike the results obtained; political narratives and cheating issues are always attached to the general election commission. The purpose of this study is to determine the role of the General Election Commission as the organizer of elections in creating a Just and Fair Election (Direct, Free, and Secret). And how the role of the Election Supervisory Board in carrying out Supervision and Implementation of laws. This study uses a descriptive quantitative approach, where data is based on survey results, document reviews, and observations. The results showed that the competence and independence of the General Election Organizers significantly influence the success of the election stages.